Senegal : Fifth Review Under the Policy Support Instrument and Request for Modification of Assessment Criterion-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
Economic performance. Growth is expected to stay high at close to 7 percent in 2017, similar to 2016, with inflation contained at 2 percent. A negative terms of trade shock combined with higher capital imports widened the current account deficit. Fiscal policy. Authorities are committed to achieving the 3 percent of GDP fiscal deficit target by the 2019 WAEMU target date--one year later than foreseen in the PSI 4th review. Delayed reforms, including to strengthen Treasury operations, and presidential elections in early 2019, are leading to increasing fiscal pressures. To keep Senegal at low risk of debt distress, structural issues underlying the public sector overall borrowing requirement (which the headline budget deficit does not fully capture), need to be addressed, through reforming the Post Office and Civil Service Pension and limiting use of deposit accounts outside budget appropriations of the current fiscal year. This will help create space for continued and much-needed investments in human and physical capital.